Chapter The Role of Higher Education in a Changing World: Why Employability Matters - Terzaroli, Carlo (Studies on Adult Learning and Education, 2018)
The transformations of work are increasingly introducing new scenarios at a global level. In fact, the disruptive importance of innovation in all workplace contexts anticipates the challenge of skills and capabilities for the work of the future. In this sense, education has a crucial role in supporting the development of students and future workers. This paper analyses in depth the link between education, work and the pedagogical instrument of work pedagogy that is derived directly from John Dewey's thought. This theoretical standpoint represents the base for the development of employability in higher education and its future challenges of innovation, development, and social inclusion